Analysis of Parental Intervention as a Contributing Factor to Marital Breakdown - Kalita Tisa Audila; Yani Achdiani; Sarah Nurul Fatimah (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
Marriage is a sacred covenant that establishes a family between a man and a woman. Within Islamic law and social norms, marriage represents the foundation of human life, forming a household built on harmony, affection, and mutual responsibility. However, the stability of a family can be disrupted by third-party intervention, particularly from parents or in-laws. Such intervention often arises from economic concerns, cultural expectations, emotional attachment, or cohabitation, which blur the boundaries between the newly formed household and the parental home. This study examines the forms, causes, and impacts of parental intervention on marital relationships. Findings indicate that parental involvement may appear in various forms such as giving advice, providing financial support, influencing decision-making, or intervening in childcare. Although often motivated by goodwill, excessive involvement can undermine the couple’s autonomy, trigger conflicts, create emotional pressure, reduce independence, and in severe cases, lead to marital breakdown or divorce. From the perspective of Islamic legal sociology, parents indeed hold a moral responsibility to guide their children. However, Islamic teachings emphasize the balance between parental guidance and respecting the independence of the married couple. Therefore, maintaining healthy communication and clear boundaries is essential to prevent conflicts and preserve marital harmony.